Experimental Study of Plastic Waste Fuel in Diesel Engine to Overcome Fuel Shortage Towards a Green Economy Facing IMO Tier III Standards - Sutrisno; Hadi Prasutiyon; Alif Rizky Saputro (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2024)
Ships generally use diesel engines as propulsion to produce energy from the combustion process. The fuel used on ships uses diesel oil, but its use can result in marine environmental pollution. Marine environmental pollution is currently a national issue that must be addressed immediately, where the International Maritime Organization (IMO) in MARPOL Annex VI TIER III limits the content of exhaust emissions. This research is to analyze the effect on engine performance and emissions, especially NOx produced by diesel engines, then compare NOx emission data with IMO TIER III standards. This research uses an experimental method by mixing two fuels with the composition B0 (pure plastic waste), B1 (80% - 20%), B2 (70% - 30%). After conducting research the effective result is B1 fuel. Because trendline graphs are quite optimal for use on diesel engines. The power produced by B1 is 1.36 KW to 2.12 KW. SFC B1 produces 431.35 g/kWh to 352.61 g/kWh. For efficiency, B1 produces 19.3% to 23.6%. For torque, bmep, and fc produce values that are directly proportional to engine speed. The results of the NOx emissions test were obtained for each type of fuel composition, B0 was 174 gr/kWh – 185gr/kWh, B1 was 182gr/kWh – 218gr/kWh and B2 was 198gr/kWh – 224gr/kWh. This meets the MARPOL Annex TIER III standards.